What treatment and services are effective for people who are homeless and use drugs? A systematic ‘review of reviews’ - Miler, Joanna Astrid; Carver, Hannah; Masterton, Wendy; Parkes, Tessa; Maden, Michelle; Jones, Lisa; Sumnall, Harry (PLOS ONE, 2021)
Background People who experience homelessness and those vulnerably housed experience disproportionately high rates of drug use and associated harms, yet barriers to services and support are common. We undertook a systematic ‘review of reviews’ to investigate the effects of interventions for this population on substance use, housing, and related outcomes, as well as on treatment engagement, retention and successful completion. Methods and findings We searched ten electronic databases from inception to October 2020 for reviews and syntheses, conducted a grey literature search, and hand searched reference lists of included studies. We selected reviews that synthesised evidence on any type of treatment or intervention that reported substance use outcomes for people who reported being homeless. We appraised the quality of included reviews using the Joanna Briggs Institute Critical Appraisal Checklist for Systematic Reviews and Research Syntheses and the Scale for the Assessment of Narrative Review Articles. Our search identified 843 citations, and 25 reviews met the inclusion criteria. Regarding substance use outcomes, there was evidence that harm reduction approaches lead to decreases in drug-related risk behaviour and fatal overdoses, and reduce mortality, morbidity, and substance use. Case management interventions were significantly better than treatment as usual in reducing substance use among people who are homeless. The evidence indicates that Housing First does not lead to significant changes in substance use. Evidence regarding housing and other outcomes is mixed. Conclusions People who are homeless and use drugs experience many barriers to accessing healthcare and treatment. Evidence regarding interventions designed specifically for this population is limited, but harm reduction and case management approaches can lead to improvements in substance use outcomes, whilst some housing interventions improve housing outcomes and may provide more stability. More research is needed regarding optimal treatment length as well as qualitative insights from people experiencing or at risk of homelessness.